PERAN JAKSA DALAM RANGKA PENEGAKAN HUKUM TERHADAP JAKSA YANG MELAKUKAN TINDAK PIDANA - Mustika Jannah (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractThe Supervisory Prosecutor has a function in accordance with article 563 of the Attorney General's Regulation Number: PER-009 / A / JA / 01/2011 concerning the Organization and Work Procedures of the Republic of Indonesia Prosecutor's Office, namely the examination of findings, reports, complaints of alleged violations of discipline, abuse of office or authority and propose the enforcement of the Attorney General's staff at the High Prosecutor's Office, the Public Prosecutor's Office or the District Attorney's Office in the jurisdiction of the High Prosecutor Office concerned, which is proven to have committed disciplinary violations or criminal offenses. The problem examined is how the supervisory prosecutor's role is in the context of law enforcement against prosecutors who commit criminal acts and what forms of supervision are conducted by supervisors in supervising prosecutors. Data analysis uses qualitative analysis. Based on the results of the study, the Supervisory Prosecutor's role in law enforcement against Prosecutors who commit criminal acts is the normative role that originates from the written regulations and existing supervisory regulations issued to maximize oversight within the prosecutor's environment, despite the overlapping authority in internal control arrangements and externally the rest according to the author is good enough to live implementation of each supervisory officer.